PENATAAN PERAN PARA PIHAK DALAM PENGELOLAAN HUTAN MANGROVE DI PERKOTAAN: STUDI KASUS PENGELOLAAN HUTAN MANGROVE DI TELUK JAKARTA - Maya Ambinari; Dudung Darusman; Hadi S Alikodra; Nyoto Santoso (Jurnal Analisis Kebijakan Kehutanan, 2016)
Mangrove forests in Jakarta Bay have been degraded and deforested, resulting in flooding, intrusion, abrasion, and reduced fishery production. Mangrove forests have the characteristics of common property resources that tend to be damaged because their rights difficult to enforces. The parties involved in carrying out their role are not optimal so that conditions remain degraded. This study was conducted to find  a form of the arrangement of the party's role in the mangrove forest management. Research conducted at Muara Angke, North Jakarta and Muara Gembong, Bekasi Regency. The results showed that key players have not made a comprehensive plan of mangrove forest management. In order to realize sustainable mangrove, it's required to increase the role of the people who originally only  as Subjects to become Key Players through community development activities. NGOs and Research Institutions need to increase the role from Crowds into Context Setters which have great impact in policy making. It is needed to form the Coordinating Team of Mangrove Ecosystem Management Strategy at the provincial and regent levels to synergize the policy and management program of mangrove ecosystems. Empowerment activities need to be carried out intensively to promote changes in the role of mangrove management.